Encountering a feminist literature review with(in) mathematics education research - Bruna Leticia Nunes Viana; Anette de Ron; Paola Valero; Kicki Skog (Prometeica)
In the encounters between researchers, the process of doing a literature review, and feminist research with(in) mathematics education, some considerations have emerged about the importance of considering the literature review as a constitutive part of the research process. A feminist literature review is not a simple literature review procedure to be applied to research that claims to be feminist. Rather, mobilizing feminist theoretical-methodological concepts, such as situated knowledge and affect as an apparatus to operate within the phenomena, allowed us to propose a different idea. The feminist literature review can be seen-sensed as an important terrain to create relationships-encounters with both research and researchers. It allows to come closer to different ways of knowing-doing research in entanglement with the literature, mathematical practices, feminisms, human beings, languages, search engines, and so on. In this terrain, we affect and are affected by the literature, and its encounters open up for new directions-connections. In this way, we may move away from existing patriarchal, excluding norms in academia.